3x² - 39x + 36
3(x²) - 3(13x) + 3(12)
3(x² - 13x + 12)
3(x² - 12x - x + 12)
3(x(x) - x(12) - 1(x) + 1(12))
3(x(x - 12) - 1(x - 12))
3(x - 1)(x - 12)
The slope of a horizontal line will have a value equal to 0:
m=0
Point-slope form of a line: we need a point (x₀,y₀) and the slope "m".
y-y₀=m(x-x₀)
We have a point ( E(3,-4) ) and the slope of this line (m=0); therefore:y
y+4=0(x-3=
y+4=0
y=-4
Answer: the equation for the horizontal line that contains the point E, would be:
y=-4
I can use the angle and the length of JH to find the length of IJ.
To do this, I look at the relationship IJ and JH have to the 52 degree angle. JH is opposite to angle I, and IJ is adjacent to angle I. Because the two side lengths are opposite and adjacent, I use the tangent function to solve this.
Tangent of an angle = the length of the opposite side / the length of the adjacent side. This is just another way to say tan(x)=opposite/adjacent
Now I can fill in what I know...
tan(52)=4.2/x
Now, I want to isolate x.
tan(52) = 4.2/x
x(tan(52))=4.2
x=4.2/tan(52)
Now I put 4.2/tan(52) into a calculator and get x = 3.3 ft
Hope this helps!
Answer:
-4 = 5
Step-by-step explanation:
9-4=5
1-5=-4
-4:5
Answer:
a couple of irrational numbers: -16±4√19, approximately {1.436, -33.436}
Step-by-step explanation:
Your question can be cast as the quadratic equation
x² +32x -48 = 0
The solutions can be found using the quadratic formula:
x = (-32 ±√(32² -4(1)(-48)))/(2(1)) = -16±√304 = -16±4√19
_____
<em>Comment on the equation we used</em>
We notice that when p and q are roots, the equation can be written ...
(x -p)(x -q) = 0 = x² -(p+q)x +pq
You want p+q = -32, pq = -48, so the equation is ...
x² -(-32)x +(-48) = 0
x² +32x -48 = 0 . . . . . . with parentheses eliminated